CORRECTION OPPORTUNITIES OF BIOCENOSIS IN CHILDREN WITH ATOPIC DERMATITIS AND RELATED FUNCTIONAL DISORDERS OF DIGESTIVE SYSTEM - S.K. Arshba; Z.N. Dzagoeva; R.M. Torshkhoeva; Yu.G. Levina; E.A. Vishneva (Педиатрическая фармакология)
The article reveals the relevance of the correction of bacterial overgrowth syndrome in children with atopic dermatitis and concomitant diseases of digestive system. The main functions of the microflora, the influence of various factors on the colonization resistance of the body of the child have been identified. The results of our own observations are cited. On their basis we proposed approaches to the treatment of children with atopy and concomitant diseases of the gastrointestinal tract. Key words: children, atopic dermatitis, microbiota, bacterial overgrowth syndrome. (Pediatric Pharmacology. — 2011; 8 (5): 114–117.)